Transfer Pricing, Bagaimana Pengaruh Perencanaan Pajak, Tunneling Incentive, Aset Tidak Berwujud, Persentase Komisaris Independen dan Debt Covenant? - Rizwan S Jama; Iqbal M. Aris Ali; Fitriani Sardju (Univiversitas Dr. Djar Wattiheluw, 2024)
The aim of this research is to examine tax planning variables, tunneling incentives, intangible assets, the portion of independent commission agents and debt arrangements that influence transfer prices. The research object is a manufacturing company listed on the Indonesian Stock Exchange. The sample was 50 companies, selected using purposive sampling techniques. Secondary data sources using multivariate linear regression analysis techniques. The research results show that tunneling incentives have a positive effect on transfer prices. Tax planning, intangible assets, percentage of independent commission agents and debt arrangements have no effect on transfer pricing.